Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli Daerah Kabupaten/Kota Di Daerah Istimewa Yogyakarta Tahun 2011-2020 - Nur Aini, Yana; Susanto, Joko; Sri Winarti, Asih (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Local Own-Source Revenue is revenue that comes from regional original economic sources. One of the steps to increase PAD is by optimizing the potential in the tourism sector. This study aims to analyze the effect of the number of tourist objects, the number of cultural attractions, the number of hotels and the number of restaurants on the districts/cities Local Own-Source Revenue in the Special Region of Yogyakarta in 2011-2020. In this study using quantitative methods. The type of data used is secondary data sourced from the Directorate General of Fiscal Balance (DJPK), and the Department of Tourism and Culture with the data used is panel data of 5 districts/cities in the Special Region of Yogyakarta. The analytical tool used is panel data regression using eviews 9, and using multiple linear regression as hypothesis testing. The results of this study indicate that the number of tourist objects and the number of hotels have a positive and significant effect on local revenue, while the number of cultural attractions and restaurants have no effect on Local Own-Source Revenue.